DNA repair dysregulation from cancer driver to therapeutic target - Curtin, Nicola J. (Nature reviews. Cancer, 2012)
Key Points The DNA damage response (DDR) coordinates the repair of DNA and the activation of cell cycle checkpoints to arrest the cell to allow time for repair. DNA is subject to a high level of endogenous damage and the DDR is essential for the maintenance of genomic stability and survival. Dysregulation of the DDR can lead to genomic instability that promotes cancer development but that is exploitable with both conventional cytotoxic therapy and DDR inhibitors. Downregulated DDR pathways render the tumour sensitive to specific cytotoxics and some DDR inhibitors. Upregulated DDR pathways confer therapeutic resistance. Inhibitors of the DDR have been developed to overcome resistance and to augment the activity of conventional therapy. Loss of a DDR pathway can lead to dependence on a compensatory pathway, and targeting this second pathway may render endogenous DNA damage cytotoxic by a process termed synthetic lethality, which will be tumour-specific because the normal tissues in the animal (or person) will have functional DNA repair. Despite promising preclinical data combining DDR inhibitors with conventional cytotoxic agents, these combinations have been less successful in the clinic and are often associated with toxicity. Exploitation of DDR defects by synthetic lethality is a more promising approach. Clinical data on the use of poly(ADP-ribose) polymerase (PARP) inhibitors in homologous recombination repair (HRR)-defective tumours are encouraging. Robust and validated biomarkers to identify DDR defects that are exploitable by both conventional cytotoxic therapy and agents targeting the DDR are needed to effectively stratify patients. The DNA damage response (DDR) is often altered in tumour cells and this Review discusses the many strategies to target the pathways that comprise the DDR as single agents and in combination to produce synthetic lethality specifically in tumour cells. Dysregulation of DNA damage repair and signalling to cell cycle checkpoints, known as the DNA damage response (DDR), is associated with a predisposition to cancer and affects responses to DNA-damaging anticancer therapy. Dysfunction of one DNA repair pathway may be compensated for by the function of another compensatory DDR pathway, which may be increased and contribute to resistance to DNA-damaging chemotherapy and radiotherapy. Therefore, DDR pathways make an ideal target for therapeutic intervention; first, to prevent or reverse therapy resistance; and second, using a synthetic lethal approach to specifically kill cancer cells that are dependent on a compensatory DNA repair pathway for survival in the context of cancer-associated oxidative and replicative stress. These hypotheses are currently being tested in the laboratory and are being translated into clinical studies